A adaptação de A Casa das Sete Mulheres: o processo de tradução intersemiótica de uma obra literária para a televisão - Prado, Izabelle Cristine Carbonar do (2010)
The topic of this research is the miniseries A Casa das Sete Mulheres, by Walter Negrão and Maria Adelaide Amaral, a version of the homonimous book by Leticia Wierzchowski, broadcasted by Rede Globo from January to April 2003. It starts from the hypothesis that the process of translation involves not only subjects of content but also medium in order to transpose the story from the source text, besides the possibility that this translation process turns the plot more dense and entangled due to the need to maintain chapters on the air for longer time to explore the audience success. The thesis attempts to understand how the communicative translation processes enrolled in socio-cultural repertoire of the mestizo societies are required to discuss the consequences of the construction procedures of soup-operas from literary works. As a general objective, approaches the intersemiotic translation of a book into a miniseries format, showing the changes in history and understanding the re-establishment of the characteristics and emotions described in the source text. It is important to observe that, between similarity and difference, the processing product must have a structure that pleases the public and enables their understanding on the whole, so it will be checked how the translation process is submitted to the entertainment features of television and how the implementation of decisions are marked by the performance of the product. Scholars of culture semiotics, communication theory, translation and creative processes are utilized to characterize the cultural procedures that are inserted into television production. The theorists of miscegenation also play an important role in the issues addressed in this study. The theoreticalmethodological approach is, at first, to conduct a brief survey on the history of soap opera in Brazil and Latin America, considering the configuration of every genre of television drama and highlighting the potential of narrative miniseries. Later are observed, as part of specific objectives, micro-comparisons between the main scenes of the book and the miniseries, focusing on the case study in which the analysis is based, illustrating the similarities and differences between the source language and target language, always considering the media culture changes - a relevant component in this study. It is also considered the state of the art of Brazilian miniseries in the national and Latin America landscape of television drama